Agenda-setting in the clinical encounter: A systematic review protocol. - Ailyn Sierpe; Renata W Yen; Gabrielle Stevens; Aricca D Van Citters; Glyn Elwyn; Catherine H Saunders (PLoS ONE)
Introduction Agenda-setting is a collaborative communication strategy used by a clinician before or at the start of a clinical encounter to work together with the patient to "elicit, propose, and organize" topics to be discussed during the encounter. While clinical visit agenda-setting has been acknowledged as an important element of patient-centered communication, the effectiveness of agenda-setting interventions in improving healthcare outcomes is unclear. To our knowledge, no systematic review has examined clinical visit agenda-setting interventions. Methods and analysis The primary aim of the systematic review will be to assess the effects of agenda-setting interventions on outcomes relating to the clinical encounter itself, patients, and clinicians, as well as any other study-specified outcomes. Our secondary aims will be to examine the characteristics and delivery attributes of agenda-setting interventions, as well as how agenda-setting has been operationalized and measured. We will search selected databases (APA PsycInfo, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Cumulative Index to Nursing and Allied Health Literature, MEDLINE via PubMed, ProQuest, Scopus, and Web of Science) and gray literature from inception until date of search. All studies comparing a clinical visit agenda-setting intervention with either usual care or another agenda-setting intervention will be included. Two independent reviewers will complete article screening and data extraction, with a third independent reviewer resolving any conflicts. We will assess all studies' methodological quality and the quality of their evidence using standardized criteria. If a sufficient number of studies report the same outcomes, we will pool their results and perform a meta-analysis of those outcomes. We will also synthesize all results qualitatively, regardless of whether we are able to complete a meta-analysis. Prospero registration number CRD42023468045.